The Historical Consumer : consumption and Everyday Life in Japan, 1850?2000 - Hunter, Janet; Francks, Penelope (Basingstoke Palgrave Macmillan, 2012)
This book explores the rise of consumerism and the expanding variety of goods available in Japan. Japan is placed within the comparative context of the 'consumer revolution' in Europe and North America, contributing to the analysis of the ways in which consumption and everyday life change in the course of economic development.
Keywords: Consumismo -- Japón